Rekonstruksi Sistem Pemerintahan Presidensiil Berdasar Undang- Undang Dasar 1945 Menuju Sistem Pemerintahan Presidensiil Murni - Sulardi, Sulardi (Mahkamah Konstitusi Republik Indonesia, 2012)
Indonesian governmental system is conducted based on 1945 Constitution. When varied constitutions were implemented in Indonesia in the past, the consequence is there were varied political systems. In 1999-2002, there were changes in 1945 Constitution. One of the objectives is to strengthen presidential system of government. It was expected that the amended Constitution could become the foundation of the good, effective, and efficient presidential system of government. In fact, the amended Constitution does not yet specified the characteristics of the presidential system of government, so there is awareness that a reconstruction into the presidential system of government is needed. Since 1945 independence until transition period, presidential system of government based on 1945 Constitution was conducted inconsistently because 1945 Constitution was arbitrarily interpreted by the presidents in their terms of office. Theoretically, there was a new concept on the presidential system of government, that is the pure presidential system of government. Practically, if the concept is included in 1945 Constitution, the consequence is that the president has relatively equal position among others state institutions. Then, the presidential system of government can effectively and efficiently run because each of state institutions, especially President and Parliament, can focus their attention to their tasks and duties.